The Benefits and Problems of Implementing Language Planning Practices at an Islamic Boarding School in Surakarta - Manik, Hemalia; Naurannisa, Herina; Musyafaah, Hindi; Morika, Kinaya; Sarosa, Teguh (English Teaching and Linguistics Journal (ETLiJ), 2024)
This article examined the challenges faced by educational institutions, especially in an Islamic Boarding School, in managing the linguistic diversity of students from various backgrounds and considered the importance of effective communication. In this context, language planning proved to be an important tool for handling language diversity. The focus of this article was on implementation of the strategic language planning within an Islamic Boarding School in Surakarta which brought about real changes in language structure and function. This research would not only discuss the benefits of the implementation of language planning that occurs at an Islamic Boarding School, but would also discuss the problems faced and try to provide appropriate solutions to overcome these problems. The article highlighted the important role of language planning in achieving a community's vision and mission and emphasized its impact on academic success and the overall community environment. This paper not only provides empirical insights into how language planning occurs in boarding schools but also contributes innovations to deal with the cultural and linguistic diversity that exists in educational settings, particularly in boarding schools. The focus of this study was valuable for educators, students, policymakers, and researchers who wanted to optimize language planning in a boarding school environment, which would increase students' effectiveness in the linguistic field. By considering how language planning works in those situations, the article provided insight into building a consistent environment that encouraged effective communication and was consistent with broader community goals.